Perancangan Tata Letak Pabrik dengan Pendekatan Kuantitatif Menggunakan Metode Algoritma Craft: STUDI KASUS CV. X - Ronanda Dias Alfaiz; A. Harits Nu'man; Iyan Bachtiar (UNISBA Press, 2023)
Abstract. Facility layout is one the factors that plays an important role in improving the smoothness of production in a company. Basicly, companies are categorized as a good company is a company that is able to organize and able to manage all the supporting aspects in the company's success. One of company‟s efforts to become a good company is to do the good design and the good facilities layout. CV. X is a manufacture industry which operate in manufacture of pharmachies machinery. Layout condition in the company of the production process flow is still irregular between work areas. This also has implications for the company's inability to maximize the company's production profits. Therefore, the company seeks to increase production targets by evaluating the layout of the existing facilities. The purpose of this research is to obtain a layout of production facilities that have better material flow and minimum material transfer from production activities. The method used in this study is a quantitative method with the CRAFT (Computer Relative Allocation of Facilities Technique) algorithm and simulated using WinQSB 2.0 software. The results showed that this method can minimize the total OMH and material displacement distance. Where the displacement distance in the initial layout is 110.75 meters, while the displacement distance in the proposed layout is 78.75 meters with the total cost according to the proposal is Rp. 217,054.79. This shows that the proposed layout can reduce the distance of moving goods by 32 meters and produce a better flow pattern for the company. Keywords: Layout, Quantitative, CRAFT, Algorithm Abstrak. Masalah tata letak fasilitas merupakan salah satu faktor penting dalam peningkatan kelancaran produksi di suatu perusahaan. Perusahaan yang dikategorikan baik salah satu syaratnya yaitu mampu mengelola proses perancangan tata letak fasilitas yang baik. CV. X merupakan suatu industri manufaktur yang bergerak di bidang pembuatan mesin untuk kebutuhan bidang farmasi. Kondisi yang terdapat pada perusahaan adalah tata letak aliran proses produksi yang masih tidak beraturan antar area kerja. Hal ini berimplikasi pada ketidakmampuan perusahaan dalam memaksimalkan keuntungan produksi perusahaan. Maka dari itu perusahaan berupaya meningkatkan target produksi hingga dengan mengevaluasi tata letak fasilitas yang ada saat ini. Tujuan dari penelitian ini adalah untuk mendapatkan tata letak fasilitas produksi dengan aliran material yang lebih baik serta pemindahan material yang minimum. Metode yang digunakan dalam penelitian ini adalah metode kuantitatif dengan algoritma CRAFT dan di simulasikan dengan menggunakan software WinQSB 2.0. Hasilnya, metode ini dapat mengurangi OMH total dan jarak perpindahan material. Dimana jarak perpindahan pada layout awal sebesar 110,75 meter, menjadi 78,75 meter pada layout usulan dengan total ongkos usulan adalah sebesar Rp217.054,79. Hal ini menunjukan bahwa layout usulan mengurangi jarak perpindahan sebesar 32 meter dan menghasilkan pola aliran yang lebih baik bagi perusahaan. Keywords: Layout, Kuantitatif, Algoritma CRAFT